Optimization Problems in Production and Planning: Approaches and Limitations in View of Possible Quantum Superiority - Zwingel, Maximilian; May, Christopher; Reitelshöfer, Sebastian; Mauerer, Wolfgang (Annals of Scientific Society for Assembly, Handling and Industrial Robotics 2023, 2025)
Modern production and process planning is characterized by complex and diffuse interrelationships of parameters, properties and control values. New materials, innovative production technologies, differing degrees of automatability and application dependency form a multidimensional problem space for optimization, which cannot be efficiently solved by today’s technologies. Approximations in form of genetic algorithms, different heuristics and simplifications exist, but lack applicability due to high runtime and estimation errors. Quantum computers, quantum annealers and hybrid algorithms show potential to offer added value and better performance over established approaches for optimization, planning and production control, but are often incomprehensible for production engineers. Based on an analysis of industrial problems in different domains and a definition of relevant problem cases, the potential of quantum systems for optimization in production and planning is explored. An approach to close the gap between classical and quantum optimization from an engineering standpoint is made by describing the transformation process for a real-world problem and discussing performance indicators of model implementation
Keywords: Production planning; Optimization; Quantum algorithms